2013
DOI: 10.7598/cst2013.407
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reduction Bahaviour of Vinclozolin Fungicide at Platinum Electrode

Abstract: The electrochemical behavior of vinclozolin [3-(3,5-dichlorophenyl)-5-methyl-5-vinyl-1,3 oxazolidine-2,4-dion] in dimethylsulfoxide was performed by cyclic voltammetry (CV) and linear sweep voltammetry (LSV). The main decomposition pathway included in the cleavage of chlorine atoms at platinum electrode. The general reduction mechanism of this compound has been suggested based on the results obtained. The peak potential and peak current were found to be depending on pH of the buffer solution. The measuring sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…In subsequent research, Hromadová and co-workers observed that the electroreductions of 12 – 14 at a mercury cathode in DMSO/TBAPF 6 involve cleavage of the carbon–chlorine bonds and formation of host–guest complexes of cyclodextrin. Sreedhar and colleagues , investigated the reduction of 12 at both mercury and platinum cathodes over a wide pH range to gain insight into the mechanism. From an investigation of the reduction of 14 in a mixture of Britton–Robinson buffer (pH 2.0–6.0) with DMF, Sreedhar and co-workers concluded that each carbonyl moiety undergoes a two-electron reduction.…”
Section: Halogenated Environmental Pollutantsmentioning
confidence: 99%
“…In subsequent research, Hromadová and co-workers observed that the electroreductions of 12 – 14 at a mercury cathode in DMSO/TBAPF 6 involve cleavage of the carbon–chlorine bonds and formation of host–guest complexes of cyclodextrin. Sreedhar and colleagues , investigated the reduction of 12 at both mercury and platinum cathodes over a wide pH range to gain insight into the mechanism. From an investigation of the reduction of 14 in a mixture of Britton–Robinson buffer (pH 2.0–6.0) with DMF, Sreedhar and co-workers concluded that each carbonyl moiety undergoes a two-electron reduction.…”
Section: Halogenated Environmental Pollutantsmentioning
confidence: 99%